2011
DOI: 10.2527/jas.2010-3056
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bovine seminal quality assessments using different viewing chambers with a computer-assisted semen analyzer1

Abstract: Computer-assisted sperm analysis of fresh and frozen-thawed bovine sperm requires proper handling and preparation, and the type of slide used in the assessment is critical if the resultant data are to be useful quality control measurements. In the present study, 4 different slide viewing chambers, a Makler chamber, a clean slide-coverslip, or a 2- or 4-cell chamber Leja slide, were compared with assess their utility in providing reliable measurements of sperm motility variables. A Hamilton-Thorne IVOS Computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 6 publications
3
41
0
4
Order By: Relevance
“…The highest quality of semen is indicated by high sperm general motility, VAP and VSL movement of sperm cells (Lenz et al, 2011;Ibănescu et al, 2016). To the best our knowledge, this is the first study that investigated the effect of EL aqueous extract added to tris-based egg yolk diluent on sperm kinetic motilities of frozen-thawed bull semen.…”
Section: Discussionmentioning
confidence: 98%
“…The highest quality of semen is indicated by high sperm general motility, VAP and VSL movement of sperm cells (Lenz et al, 2011;Ibănescu et al, 2016). To the best our knowledge, this is the first study that investigated the effect of EL aqueous extract added to tris-based egg yolk diluent on sperm kinetic motilities of frozen-thawed bull semen.…”
Section: Discussionmentioning
confidence: 98%
“…Sperm motility results obtained with CASA are dependent on many factors (see Amann and Waberski 2014) including some CASA system settings and preparation of semen samples for analysis (Rijsselaere et al 2003, Contri et al 2010, Broekhuijse et al 2011. A considerable effect, which has received particular attention recently, can be exerted by the type of counting chamber, which was reported in humans (Le Lannou et al 1992) and in some species of animals (Iguer-Ouada and Verstegen 2001, Massányi et al 2008, Contri et al 2010, Lenz et al 2011, Hoogewijs et al 2012, Gloria et al 2013, Palacín et al 2013). The present study demonstrates that chamber type influences sperm concentration results and sperm motility parameters obtained with CASA also in the case of boar semen.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of using different chambers may hinder the identification and quantification of factors potentially affecting CASA outcomes, and there is also a need to harmonize and standardize laboratory procedures used during CASA assessment for each species (Rijsselaere et al 2003, Broekhuijse et al 2011, Gloria et al 2013. In a previous research, the effect of the type of chamber used has been studied both in man (Le Lannou et al 1992) and in some animal species such as bulls (Contri et al 2010, Lenz et al 2011, Gloria et al 2013, rams (Palacín et al 2013), horses (Hoogewijs et al 2012), rabbits (Massányi et al 2008) and dogs (Iguer-Ouada and Verstegen 2001). However, little is known about the effect of different chambers designed for CASA analysis on the sperm concentration and especially on kinetic evaluation of boar spermatozoa.…”
mentioning
confidence: 99%
“…may affect sperm motility. Increased sperm motility has been observed in the middle of the chamber, than at its edges, due to passive movement of dead and immotile spermatozoa to the outer area of the coverslip (Lenz et al, 2011). Variations may also occur when different chambers are used.…”
Section: Ram Semenmentioning
confidence: 99%
“…Variations may also occur when different chambers are used. Lenz et al (2011) evaluated sexsorted frozen thawed bull semen and reported that approx. 25% more total and progressive motility in Makler chamber or common slides with coverslips compared to Leja slides; however, they recorded no differences between Makler and common slides with coverslips.…”
Section: Ram Semenmentioning
confidence: 99%